2009
DOI: 10.1007/s11999-009-0846-2
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effect of Autograft and BMP-7 in the Treatment of Atrophic Nonunions

Abstract: Combining autologous bone graft and recombinant human bone morphogenetic protein-7 (BMP-7) to treat long-bone fracture aseptic atrophic nonunions theoretically could promote bone healing at higher rates than each of these grafting agents separately. We retrospectively reviewed prospectively collected data on patient general characteristics, clinical outcomes, and complications over 3 years to determine the healing rates and the incidence of complications and adverse events of this ''graft expansion rationale.'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 51 publications
2
61
0
10
Order By: Relevance
“…On the other hand, this literature research also revealed that most of the clinical findings are based on case reports or case series with small patient populations, characterized by different delivery approaches, anatomical locations, bone pathologies and dosages, which makes it difficult to draw any final conclusion about the real potential of BMPs therapy and the best protocol they can be applied to [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. Therefore, further research in this direction is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, this literature research also revealed that most of the clinical findings are based on case reports or case series with small patient populations, characterized by different delivery approaches, anatomical locations, bone pathologies and dosages, which makes it difficult to draw any final conclusion about the real potential of BMPs therapy and the best protocol they can be applied to [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. Therefore, further research in this direction is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 6.2 million fractures occurring annually in the United States, 5 to 10% on average develop into delayed unions or non-unions with great expenditure for the national health system in terms of costs and work force loss [47]. In this scenario, BMPs have been suggested as a promising treatment approach for bone repair, since they are considered the most potent osteoinductive agents [68].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies directed specifically at the use various recombinant BMPs have failed to show an association with the development of tumor induction, systemic toxicity, or allergic reaction to BMP in a short-term or intermediate-term follow-up period. 2,6,8,10,12,14,[16][17][18][19] Furthermore, several studies have shown that the use of hBMP in the treatment of non-unions and acute open fractures may be associated with a decreased risk of infection compared to control groups. 7,12 Although the mechanism for this has not been fully elucidated, researchers suggest that this may be linked to the positive effect that BMPs exert on the local cellular environment and the vascularity by stimulating angiogenesis at the fracture site.…”
Section: Discussionmentioning
confidence: 99%
“…10 The osteoinductive properties of BMP have been well documented to not only enhance the amount of new bone formed, but to increase the rate at which fracture healing occurs. 2,11,12 As a result, the use of BMP in bone fusion and spinal arthrodesis continues to increase in volume.…”
Section: Introductionmentioning
confidence: 99%
“…Rekombinan kemik morfojenik proteini (BMP) hem hayvan hem klinik çalışmalarla geliştirilmiş ve başarıy-la kullanılmıştır. [31,32] Klavikula kaynamamaları ile ilgili mevcut literatür bilgisi yetersiz olmakla beraber, atrofik kaynamamalarda biyolojik destek amaçlı makul bir seçenek olabilir.…”
Section: Adjuvan Tedavi Seçenekleriunclassified